PLGA and PDMS-based in situ forming implants loaded with rosuvastatin and copper-selenium nanoparticles: a promising dual-effect formulation with augmented antimicrobial and cytotoxic activity in breast cancer cells - Maged, Amr; Mabrouk, Mostafa; Nour El-Din, Hanzada T.; Osama, Lamyaa; Badr-Eldin, Shaimaa M.; Mahmoud, Azza A. (Frontiers in Pharmacology, 2024)
Breast cancer is among the most prevalent tumors worldwide. In this study, in-situ forming implants (ISFIs) containing rosuvastatin calcium were prepared using three types of poly(D, L-lactic-co-glycolic acid) (PLGA), namely, PLGA 50/50 with ester terminal and PLGA 75/25 with ester or acid terminal. Additionally, polydimethylsiloxane (PDMS) was added in concentrations of 0, 10, 20, and 30% w/v to accelerate matrix formation. The prepared ISFIs were characterized for their rheological behaviors, rate of matrix formation, and in-vitro drug release. All the prepared formulations revealed a Newtonian flow with a matrix formation rate between 0.017 and 0.059 mm/min. Generally, increasing the concentration of PDMS increased the matrix formation rate. The prepared implants' release efficiency values ranged between 46.39 and 89.75%. The ISFI containing PLGA 50/50 with 30% PDMS was selected for further testing, as it has the highest matrix formation rate and a promising release efficiency value. Copper-selenium nanoparticles were prepared with two different particle sizes (560 and 383 nm for CS1 and CS2, respectively) and loaded into the selected formulation to enhance its anticancer activity.The unloaded and loaded implants with rosuvastatin and copper-selenium nanoparticles were evaluated for their antibacterial activity, against Gram-positive and negative microorganisms, and anticancer efficacy, against MCF-7 and MDA-MB-231 cell lines. The results confirmed the potency of rosuvastatin calcium against cancer cells and the synergistic effect when loaded with smaller particle sizes of copper-selenium nanoparticles. This formulation holds a considerable potential for efficient breast cancer therapy.